2004
DOI: 10.1074/jbc.m407153200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Menaquinone-dependent Disulfide Bond Formation Pathway of Escherichia coli

Abstract: In the protein disulfide-introducing system of Escherichia coli, plasma membrane-integrated DsbB oxidizes periplasmic DsbA, the primary disulfide donor. Whereas the DsbA-DsbB system utilizes the oxidizing power of ubiquinone (UQ) under aerobic conditions, menaquinone (MK) is believed to function as an immediate electron acceptor under anaerobic conditions. Here, we characterized MK reactivities with DsbB. In the absence of UQ, DsbB was complexed with MK8 in the cell. In vitro studies showed that, by binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…Indeed, a series of our mutational analyses indicated that the quinone transition takes place whenever Cys-44 is unpaired. Consistent with the involvement of Cys-44, the transition is sensitive to a thiol modification agent and to pH changes, giving an apparent pK a of Ϸ6.6 expected for thiolate deprotonation (6,16).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Indeed, a series of our mutational analyses indicated that the quinone transition takes place whenever Cys-44 is unpaired. Consistent with the involvement of Cys-44, the transition is sensitive to a thiol modification agent and to pH changes, giving an apparent pK a of Ϸ6.6 expected for thiolate deprotonation (6,16).…”
mentioning
confidence: 69%
“…We have characterized reactivities and properties of DsbB that is free from any bound quinones (11), of DsbB that bears UQ (16), and of DsbB that bears menaquinone (6). These analyses taken together revealed that there are two pathways of DsbB͞ quinone-mediated oxidation of DsbA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bekker et al (6) reported significant changes in both size and redox state of the Q pool when the environment changes from a well aerated environment to an environment with low oxygen availability. Some respiratory components that intrinsically interact with Q are capable of catalyzing redox reactions with both UQ and MQ (7)(8)(9)(10)(11). Such interactions may be important in physiological and evolutionary aspects in addition to enzymatic function.…”
mentioning
confidence: 99%
“…Arg48 substitutions in DsbB result in a low-activity enzyme that can no longer utilize the MK analog menadione as an in vitro electron-accepting substrate (Kadokura et al, 2000). MK-8 has been shown to associate with DsbB, similar to that of UQ, by spectroscopic analysis (Takahashi et al, 2004). The in vitro reaction of DsbA oxidation with MK-8 has been shown to be slower than the UQ-dependent reaction.…”
Section: Menaquinone Work As An Electron Acceptor In the Dsba-dsbb Smentioning
confidence: 99%